Future of Reinforced Concrete Design Codes: Challenges and Perspectives - Mikalai A. Rak; Viktar V. Tur (Железобетонные конструкции)
The article presents a brief analysis of the experience of developing standards for the design of reinforced concrete structures in the Republic of Belarus. The principles on the basis of which these norms were developed are considered. The advantages and disadvantages of using European design standards EN 1992-1-1 of various generations, as well as fib Model Codes are shown.